Paper Cuts - Elroy Ayer; Council Grove Daily Appeal (Symphony in the Flint Hills, 2019)
Introduction: The worth and service of the cowboy is not justly estimated by the people of the East who have generally regarded him as a wild semi-desperado...He is as weather-wise as a mariner and by the position of the Big Dipper from the north star at night can tell very near the correct time. (Excerpted from: Lawrence Daily World, (Lawrence, Kansas), Elroy Ayer, 3 June 1908; and "Value of the North Star", Council Grove Daily Appeal, (Council Grove, Kansas), 29 December 1904.